Surgical Management of Non-Metastatic Pancreatic Cancer in the United Kingdom: Results of a Nationwide Survey on Current Practice - Gemenetzis, Georgios; McKay, Siobhan; Pathak, Samir; Moir, John; Laing, Richard; Jamieson, Nigel B.; Young, Alastair L.; Chatzizacharias, Nikolaos A.; Giovinazzo, Francesco; Roberts, Keith J. (Frontiers in Oncology, 2021)
Background: It is presently unclear what clinical pathways are followed for patients with non-metastatic PDAC in specialised centres for pancreatic surgery across the United Kingdom (UK). Methods: Between August 2019 and August 2020 an electronic survey was conducted aiming at a national cohort of pancreatic surgeons in the UK. Participants replied to a list of standardised questions and clinical vignettes, and data were collected and analysed focusing on management preferences, resectability criteria, and contraindications to surgery. Results: Within the study period, 65 pancreatic surgeons from 27 specialist centres in the UK (96%) completed the survey. Multidisciplinary team meetings are utilised universally for the management of patients with PDAC, however, different staging systems for resectability classification are being applied. In borderline resectable PDAC, most surgeons were keen to proceed with surgical exploration post NAT, but differences were noted in preferred chemotherapy regimens. Surgeons from standard volume institutions performed fewer vein resections annually and were more likely to deem patients with locally advanced PDAC as unresectable. Intra-institutional variability in patient management was also present and ranging between 20-80%. Conclusions: Significant variability in the surgical management of non-metastatic PDAC was identified both on inter- and intra-institutional level.